(untitled) - Straubhaar, Joseph (Australia, 2004)
Do your students understand how they are affected by the media they use? Do they understand how technology works, develops and changes over time. MEDIA NOW is the first mass communication text to encourage students to think critically about the media and its effects on culture and also provide them with a thorough understanding of how the media technologies develop, operate, converge and affect our greater society. Unlike other introductory mass communication books, MEDIA NOW prepares students for their careers in the expanded field of telecommunications, interactive media, and traditional media industries, by providing them with a book that will not only excite them but teach them the foundational theories, concepts and technical knowledge to help them thrive. MEDIA NOW: UNDERSTANDING MEDIA, CULTURE AND TECHNOLOGY is that book!
Keywords: Telecommunication,Information technology,Mass media; United states,United states,United states